Mitochondrial haplogroups and control region polymorphisms are not associated with prostate cancer in Middle European Caucasians. - Edith E Mueller (Public Library of Science (PLoS), 2009)
Background Besides being responsible for energy production in the cell, mitochondria are central players in apoptosis as well as the main source of harmful reactive oxygen species. Therefore, it can be hypothesised that sequence variation in the mitochondrial genome is a contributing factor to the etiology of diseases related to these different cellular events, including cancer. The aim of the present study was to assess the frequency of haplogroups and polymorphisms in the control region (CR) of mitochondrial DNA of peripheral blood mononuclear cells from patients with prostate carcinoma (n = 304) versus patients screened for prostate disease but found to be negative for cancer on biopsy (n = 278) in a Middle European population. Methodology/principal findings The nine major European haplogroups and the CR polymorphisms were identified by means of primer extension analysis and DNA sequencing, respectively. We found that mitochondrial haplogroup frequencies and CR polymorphisms do not differ significantly between patients with or without prostate cancer, implying no impact of inherited mitochondrial DNA variation on predisposition to prostate carcinoma in a Middle European population. Conclusions/significance Our results contrast with a recent report claiming an association between mtDNA haplogroup U and prostate cancer in a North American population of caucasian descent.